Hydrodynamic cavitation effects on advanced oxidation processes and mass transfer: A conceptual model - Fleite, S.N.; Ayude, M.A.; Ranade, V.V.; Cassanello, M.C. (Chemical engineering journal advances, 2024)
•Conceptual model to analyze results of hydrodynamic cavitation (HC).•Integrates the presence of supercritical water (SCW) to explain bubble collapse dynamics.•HC effect on aqueous solutions of polymeric, ionic, and volatile organic compounds.•Model applied to interpret results in SCW oxidation reactors and HC effect on other processes. Advanced oxidation process (AOPs) technologies are the subject of intense research due to the need for treating refractory wastewaters. Among them, hydrodynamic cavitation (HC) is particularly well-studied because of its potential as an AOP and as a means of intensification for other processes, including other AOPs. Understanding HC and its effects is crucial for its development and practical application. This study introduces a conceptual model that integrates the presence of supercritical water (SCW) to interpret HC results. The model was validated by selected experimental scenarios focused on exploring the impact of HC on the viscosity of a soluble polymer solution, the precipitation of an ionic salt from an unsaturated solution, and the stripping of volatile organic compounds (VOCs). The results were analyzed and interpreted using the conceptual model, remarking the scenarios that cannot be explained by the generally accepted mechanisms of radicals’ formation or pyrolysis. Furthermore, the model was then applied to analyze the trends reported in the existing literature regarding the application of HC as an AOP and as a method of intensification. The occurrence of SCW as a key driving force for HC chemical and physical effects represents a novel approach with the potential to enhance the design and operation of HC systems, particularly when tailoring operating conditions to maximize SCW occurrence.